2022
DOI: 10.1016/j.jpap.2021.100107
|View full text |Cite
|
Sign up to set email alerts
|

UV and violet light can Neutralize SARS-CoV-2 Infectivity

Abstract: We performed an in-depth analysis of the virucidal effect of discrete wavelengths: UV-C (278 nm), UV-B (308 nm), UV-A (366 nm) and violet (405 nm) on SARS-CoV-2. By using a highly infectious titer of SARS-CoV-2 we observed that the violet light-dose resulting in a 2-log viral inactivation is only 10 4 times less efficient than UV-C light. Moreover, by qPCR (quantitative Polymerase chain reaction) and fluorescence in situ hybridization (FISH) approach we verified that the viral titer typi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…This is similar to other results of 1.2 to 5.0 mJ/cm 2 for 1-log inactivation published in [55]- [57]. In recent experimental results, a wavelength of 278 nm at an energy density dose of 2.07 mJ/cm2 was found to result in an inactivation of 2-Log (1% of the irradiated viruses remained unaffected) [58]. The same Log reduction was achieved by a dose of 10 mJ/cm2 at 265 nm [59] and by a dose of 2 mJ/cm2 , and 4 mJ/cm2 using 270 nm and 282 nm respectively [54].The wide range of power densities, irradiation time, and energy density published by researchers can be attributed to the various virus sizes, used wavelengths, and experimental environments.…”
Section: B the Total Powersupporting
confidence: 91%
“…This is similar to other results of 1.2 to 5.0 mJ/cm 2 for 1-log inactivation published in [55]- [57]. In recent experimental results, a wavelength of 278 nm at an energy density dose of 2.07 mJ/cm2 was found to result in an inactivation of 2-Log (1% of the irradiated viruses remained unaffected) [58]. The same Log reduction was achieved by a dose of 10 mJ/cm2 at 265 nm [59] and by a dose of 2 mJ/cm2 , and 4 mJ/cm2 using 270 nm and 282 nm respectively [54].The wide range of power densities, irradiation time, and energy density published by researchers can be attributed to the various virus sizes, used wavelengths, and experimental environments.…”
Section: B the Total Powersupporting
confidence: 91%
“…This striking loss would seem to suggest that SARS2 is very sensitive to UVA radiation, and yet the recent UV action spectrum study showed that SARS2 is much more stable than other RNA viruses, such as IAV, when exposed to UVA radiation and that a 2 log reduction in SARS2 loading would require at least 12 h irradiation with 0.25 mW cm −2 UVA, not the apparent 3 h observed here, see Fig. 7 [ 56 ]. A likely major contributor to the loss of infectivity exhibited by the influenza A viruses, WSN and PR8, is the incident UV radiation which can cause damage in viral lipids, proteins and DNA.…”
Section: Resultsmentioning
confidence: 74%
“…Indeed, a recent study of the UV action spectrum for the deactivation of SARS2 revealed 278 nm radiation (UVC) was ca. 10,000 times more effective than either 365 (UVA) or 405 (visible) nm radiation [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Biasin et al, it was shown that a UV dose of only 3.7 mJ/cm 2 resulted in >3 log inactivation of the SARS-CoV-2 virus, and complete inactivation was observed with 16.0 mJ/cm 2 . In another study by the same authors, it was realized that the violet light (405 nm) dose resulting in a 2 log viral inactivation was 10 4 times less efficient than UV-C (278 nm) light, a plausible explanation for the reduced incidence of the viral infection observed during the summer. By comparing the inactivation efficiency of UVC light on porous and nonporous surfaces contaminated with the SARS-CoV-2 virus, Tomás et al realized that higher viral inactivation efficiencies were observed for nonporous surfaces than on porous surfaces.…”
Section: Introductionmentioning
confidence: 98%